Chiral Display of Pyrenes on a Peptoid Backbone: Conformational Homogeneity of Peptoid Controls Excimer Chirality - Jinyoung Oh; Yongmoon Lee; Gahee Noh; Dongcheol Park; Hohjai Lee; Junseong Lee; Changsoon Kim; Jiwon Seo (Small Structures, 2024)
Controlling chromophore chirality in three‐dimensional space is crucial for understanding the structure–chiroptical relationship. Such control enables the prediction of ideal materials for use in chiral photonic applications. In this study, optically active multipyrene systems are synthesized on peptoids. Pyrene‐based chiral submonomers, (S)‐ and (R)‐1‐pyrenylethylamine (s1pye and r1pye), are successfully incorporated into peptoids as the respective (S)‐ and (R)‐N‐(1‐pyrenylethyl)glycine (Ns1pye and Nr1pye) units. NMR spectroscopy revealed length‐ and N‐acetylation‐dependent conformational homogeneity enhancement in solution, stabilizing cis‐amides in Ns1pye‐containing peptoids. The X‐ray crystal structure of Ns1pye tetramer displayed a polyproline type‐I (PPI)‐like helix. All of the pyrene‐related absorptions are circular dichroism (CD) active, and the CD signal related to the long‐axis‐polarized transition increased with helical stabilization. Intramolecular excimer generation yielded significant circularly polarized luminescence (CPL) in the excimer emission region. Early‐stage peptoids emitted left‐handed CPL, but upon acquiring a PPI‐like helix character, CPL handedness became inverted. The CPL dissymmetry factor (glum) was comparable or superior (10−2) to that of chiral organic dyes (10−5–10−2). This new class of helical pyrene‐containing peptoids provides a CPL‐active intramolecular excimer, modulating optical activity through peptoid secondary structure homogeneity.